HKS Misinfo Review 2021
DOI: 10.37016/mr-2020-57
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 misinformation and the 2020 U.S. presidential election

Abstract: Voting is the defining act for a democracy. However, voting is only meaningful if public deliberation is grounded in veritable and equitable information. This essay investigates the politicization of public health practices during the Democratic primaries in the context of the 2020 U.S. presidential election, using a dataset of more than 67 million tweets. We find the public sphere on Twitter is politically heterogeneous and the majority—liberal and conservative alike—advocates for wearing masks and vote-by-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 24 publications
0
44
0
2
Order By: Relevance
“…Conservative users also tended to share more known conspiracy-related narratives [7]. We have also observed that there are highly connected conservative users that are more prone to spread public health and voting misinformation [2]. During the 2020 Presidential election, the incumbent former President Trump, faced little difficulty in securing the Republican nomination.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Conservative users also tended to share more known conspiracy-related narratives [7]. We have also observed that there are highly connected conservative users that are more prone to spread public health and voting misinformation [2]. During the 2020 Presidential election, the incumbent former President Trump, faced little difficulty in securing the Republican nomination.…”
Section: Discussionmentioning
confidence: 66%
“…Joe Biden officially accepted the Democratic nomination during the Democratic National Convention. 2 Donald Trump officially accepted his nomination on August 27, 2020, during the Republican National Convention. 3 As the final sprint to election day on November 3, 2020 began, Americans took to online social platforms to voice their opinions and engage in conversation surrounding the elections.…”
Section: Introductionmentioning
confidence: 99%
“…Automation offers scholars not only the opportunity to improve existing practices, but also to vastly expand the scope of data that can be collected and studied, thus potentially opening up new research frontiers within the field of socio-political events, such as political violence and social movements. Event information collection has long been a challenge for the NLP community as it requires sophisticated methods in defining event ontologies, creating language resources, and developing algorithmic approaches (Pustejovsky et al, 2003;Tanev et al, 2008;Emanuela, 2018;Chen et al, 2021). We believe that this workshop and the shared task contribute strongly towards putting emphasis on this important technology, providing a gathering point for scientists and developers in NLP, AI, conflict studies and related areas.…”
Section: Introductionmentioning
confidence: 93%
“…Ainda que muito importantes, nos parece claro que as páginas estáticas nos sites de órgãos públicos de saúde e de iniciativas isoladas no setor privado, que pretendem estimular a busca ativa e embasada da população, não dão conta dos desafios comunicacionais contemporâneos no combate às fake news. Por óbvio, o uso das fake news, tendo as informações de saúde como vítimas, não é uma particularidade brasileira ou encontra na temática do câncer seu alvo exclusivo, como constata-se nas aberrações narrativas em torno da doença pelo coronavírus 2019 (do inglês, coronavirus disease 2019 -Covid-19) nos Estados Unidos, com fortes colorações políticas, mostradas, por exemplo, por Chen et al 3 .…”
Section: Novas Habilidades Para O Mesmo Compromisso éTicounclassified
“…Qualquer um passou a poder produzir conteúdo, que quase sempre arbitrariamente é batizado com o nome de "informação" ou "notícia". Entretanto, farto material recentemente investigado, em campos distintos do saber, como o da Sociologia 3 , da Comunicação 4 e da Matemática 5 , entre outros, mostraram que, mais uma vez, a eterna promessa de superação das barreiras discursivas entre e no interior de comunidades nacionais não se confirmou. Longe disso.…”
Section: Introductionunclassified